Productivity and credibility in industry equilibrium. - Powell, Michael (RAND Journal of Economics (Wiley-Blackwell))
I analyze a model of production in a competitive environment with heterogeneous firms. Efficient production requires individuals within the organization to take noncontractible actions for which rewards must be informally promised rather than contractually assured. The credibility of such promises originates from a firm's future competitive rents. In equilibrium, heterogeneous firms are heterogeneously constrained, and competitive rents are inefficiently concentrated at the top. I explore several policy and empirical implications of this result.